Optimization of Sorghum, Moringa Leaf, and Bran Flours in the Making of Cookies High in Protein and Fiber - Wulandari, Endah; Harlina, Putri Widyanti; Arifin, Heni Radiani; Salsabila, Yufi Anandia (AgriHealth: Journal of Agri-food, Nutrition and Public Health, 2026)
The high prevalence of stunting and low fiber intake among toddlers in Indonesia led to the development of cookies as a supplementary food to support adequate protein and fiber intake. Therefore, this study aims to determine the optimal cookie formulation based on sorghum, moringa leaf, and bran flours. This study used an experimental method based on response surface methodology (RSM) with a central composite design (CCD). The resulting responses were protein (Y1) and crude fiber (Y2), which were maximized. The optimal formula for cookies was 29.04% sorghum, 2.34% moringa leaf, and 18.74% bran flours. This formulation produces cookies with protein content of 10.01%, crude fiber of 2.36%, moisture of 4.89%, ash of 3.21%, fat of 22.29%, and carbohydrate of 59.61%. The physical characteristics were hardness 4,219.53 g, fracturability 5.62 mm, °hue 84.15, and sensory with an attractive overall appearance. The results indicate that the cookies’ protein and fiber content met the supplementary food requirements of the Ministry of Health, Republic of Indonesia. However, the values were lower than predicted by the optimization, while maintaining favorable physical, chemical, and sensory characteristics.